Gestión de tesorería y eficiencia de la ejecución presupuestal en la Municipalidad Distrital de Capelo, 2023 - Cruzalegui Fonseca, Alfredo (2023)
The objective of my research is to establish how Treasury management is related to the budget execution of the District Municipality of Capelo, 2023. This research is quantitative. The most important result and that over sales is the value of 0.629** Pearson, this would indicate a The objective of our research is to establish how Treasury management is related to the budget execution of the District Municipality of Capelo, 2023. This research is quantitative. The most important result and the one that you get out of is the value of 0.629** Pearson, this would indicate a medium positive correlation.